Interface Microstructure Investigation of Babbitt-Carbon Steel Composite Using Flux with Glycerol and Petroleum Jelly Additives - Fathy, N. (Engineering, Technology & Applied Science Research, 2018)
The influence of adding glycerol and petroleum jelly during the tinning process of steel shell base of Babbitt-steel bimetal is studied in this paper. The morphology of interface layer is changed from a discontinuous layer in case of using flux+tin to a continuous one by adding glycerol or petroleum jelly to the flux+tin mixture. Also, the nterface layer thickness and the unbonded interface layer area increase by adding glycerol or petroleum jelly to flux+tin mixture due to their physical properties.